Post-Replication Repair Suppresses Duplication-Mediated Genome Instability - Putnam, Christopher D.; Hayes, Tikvah K.; Kolodner, Richard D. (PLOS Genetics, 2010)
RAD6 is known to suppress duplication-mediated gross chromosomal rearrangements (GCRs) but not single-copy sequence mediated GCRs. Here, we found that the RAD6- and RAD18-dependent post-replication repair (PRR) and the RAD5-, MMS2-, UBC13-dependent error-free PRR branch acted in concert with the replication stress checkpoint to suppress duplication-mediated GCRs formed by homologous recombination (HR). The Rad5 helicase activity, but not its RING finger, was required to prevent duplication-mediated GCRs, although the function of Rad5 remained dependent upon modification of PCNA at Lys164. The SRS2, SGS1, and HCS1 encoded helicases appeared to interact with Rad5, and epistasis analysis suggested that Srs2 and Hcs1 act upstream of Rad5. In contrast, Sgs1 likely functions downstream of Rad5, potentially by resolving DNA structures formed by Rad5. Our analysis is consistent with models in which PRR prevents replication damage from becoming double strand breaks (DSBs) and/or regulates the activity of HR on DSBs.